Oxidative stress parameters in women and men with suicidal thoughts and following a suicide attempt - Lech, Magdalena; Ostrowska, Lucyna; Waszkiewicz, Napoleon; Kułak-Bejda, Agnieszka; Maciejczyk, Mateusz; Witczak-Sawczuk, Katarzyna; Zalewska, Anna; Dańkowska, Karolina; Żendzian-Piotrowska, Małgorzata (Frontiers in Psychiatry, 2024)
This study aimed to evaluate oxidative stress parameters in individuals with depression and schizophrenia, considering gender differences, and manifesting suicidal behavior, encompassing thoughts without a tendency to be realized, thoughts with a tendency to be realized, and suicide attempts. From among the patients from Department of Psychiatry 120 individuals were selected who met the inclusion criteria and did not meet the exclusion criteria for the study. In the initial phase of the project, patients eligible for the study underwent the M.I.N.I 7.0.2 questionnaire (Mini International Neuropsychiatric Interview). Subsequently, in the second phase of the research, venous blood samples were collected from the patients for the purpose of conducting biochemical assessments, focusing on oxidative stress parameters. The study results were statistically analyzed using the STATISTICA 13.0 test and the R-project test. Redox biomarkers TOS (total oxidation state) and OSI (TOS/TAC ratio) could prove valuable in diagnosing women at a genuine risk of committing suicide. On the other hand, antioxidant parameters -SOD (Cu-Zn-superoxide dismutase), GPx (glutathione peroxidase), and GSH (reduced glutathione )may be instrumental in identifying patients with suicidal behaviors, without specifying their intensity.